(3Hjf GdfXQjI h GdJWHjbs - (3RjO efjQ(B, (3YHhjs; (3MQjR SGej eMeO gTGe(B, s ((3YeGf(B:s (3OGQ GdTQhb ddfTQ h GdJhRjY(B,s, 2006)
(3bSe GdcJGH Gdi KeGfjI aUhd SLd ajgG JegjOG eNJUQG dcd aU hgj Ydi GdfMh GdJGdj (B: (3ebOeI(B-(3GdaUd GdChd (B: (3eONd Edi GdcJGH (B: (3JYQja GdEOGQI GdYGeI (B: (3XghQYde GdEOGQI GdYGeI (B: (3eOGQS GdEOGQI GdYGeI (B: (3NUGFU GdEOGQI GdYGeI hGNJdGagG eY EOGQI GdCYeGd (B: (3GdeSDhdjI GdEOGQjI hCNdGbjGJ GdEOGQI GdYGeI (B: (3eGgjI Gdbje hGdCNdGbjGJ(B-(3GdaUd GdKGfj (B: (3GddGeQcRjI GdEbdjejI (B((3GdEOGQI GdeMdjI(B) (3aj GdCQOf (B: (3JegjO (B: (3GdQDi hGdGSJQGJjLjGJ GdeSJbHdjI ddEOGQI GdYGeI aj GdCQOf (B: (3JfXje GdEOGQI GdeMdjI (B: (3OhQ GdRef aj GJNGP GdbQGQJ GdEOGQjI(B-(3GdaUd GdKGdK (B: (3EOGQI hGJNGP GdbQGQJ (B: (3JegjO (B: (3GdbQGQ eagheg hCfhGYg hUaGJ GdebQQ (B: (3GdTaGajI (B: (3UfY GdbQGQ (B: (3YUQ GdeYdheGJjI aj GJNGP GdbQGQ (B: (3hKjbI GdCQOf ChdG(B-(3GdaUd GdQGHY (B: (3EOGQI TDhf GdehXajf hhGLHGJge (B: (3JegjO (B: (3EOGQI TDDf GdehXajf aj MGXQG heSJbHdG (B: (3hGLHGJ GdehXajf hGdCYeGd GdeMXhQI Ydjge(B-(3GdaUd GdNGeS (B: (3GdJOQjH aj GdEOGQI (B: (3JegjO (B: (3GdJOQjH aj GdEOGQI (B: (3eagheg hOhQg hCgOGag (B: (3eRGjG JOQjH hJWhjQ GdehXajf (B: (3JMOjO GdGMJjGLGJ GdJOQjHjI (B: (3GbJQGMGJ GdJOQjH(B-(3GdaUd GdSGOS (B: (3GdQbGHI aj GdEOGQI GdYGeI (B: (3JegjO (B: (3GdQbGHI (B: (3eaghegG hCgejJgG hCgOGagG (B: (3hSGFd GdQbGHI GdEOGQjI Ydi CYeGd GdEOGQI GdYGeI (B: (3JUfja GdQbGHI(B-(3GdaUd GdSGHY (B: (3JegjO (B: (3GdVQjHI (B: (3JYQjagG haQhVgG hCfhGYgG (B: (3GdehGRfI GdYGeI cCOGA Ydi GdeGdjI(B-(3GdaUd GdKGef (B: (3GdJfXje aj GdEOGQI GdYGeI (B: (3JegjO (B: (3GdJfXje GdQSej hZjQ GdQSej (B: (3NUGFU GdeMdd GdEOGQj(B.s
(3HjHdjhZQGajG U(B.253s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQI GdYGeIs